2021
DOI: 10.5489/cuaj.7521
|View full text |Cite
|
Sign up to set email alerts
|

How the COVID-19 pandemic changed postoperative infections in urology wards: A retrospective cohort study from two urology departments

Abstract: Introduction: We aimed to compare the rate of postoperative infection and drug-resistant organism (DRO) before and during the COVID-19 pandemic in urology departments. Methods: A retrospective cohort study was carried out. Data from all elective surgical procedures carried out in two urology departments between April and June 2018 and the homologous period in 2020 were collected. Main outcomes were the number of postoperative infections during the pandemic, and the number of DROs. Sample size was calculated ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The incidence of MDR UTIs in CoV patients in our study was higher than the rate reported by other studies of MDR UTIs in hospitalized patients during the pandemic [ 2 , 4 , 8 , 9 ], but was similar to the rate reported by other studies of MDR UTIs in CoV patients [ 3 , 6 ]. This increased incidence in our clinic can be explained by the dramatic decrease in the scheduled elective admissions, being up to 50% monthly.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The incidence of MDR UTIs in CoV patients in our study was higher than the rate reported by other studies of MDR UTIs in hospitalized patients during the pandemic [ 2 , 4 , 8 , 9 ], but was similar to the rate reported by other studies of MDR UTIs in CoV patients [ 3 , 6 ]. This increased incidence in our clinic can be explained by the dramatic decrease in the scheduled elective admissions, being up to 50% monthly.…”
Section: Discussionsupporting
confidence: 85%
“…The increase in antibiotic resistance and the occurrence of urinary tract infections associated with MDR gut microbiota represent an important public health problem that increases patient morbidity and mortality [ 1 ]. According to some authors, the CoV pandemic led to a decrease in the incidence of MDR UTIs [ 2 , 3 ], which can be attributed to strict isolation and hygiene measures, whereas other authors found similar rates of occurrence of MDR UTIs [ 4 , 5 , 6 ]. There is limited information on the characteristics of MDR UTIs in CoV patients, as well as on how the COVID-19 pandemic altered the profile of MDR UTI patients.…”
Section: Introductionmentioning
confidence: 99%
“…4 It is unclear whether this impact has any effect on postoperative infections in patients undergoing orthopaedic surgery in the first 90 days after COVID-19 infection. A recent study by Teixeira et al 13 found that there was no difference in rates of postoperative infection in patients undergoing urologic surgery during the COVID-19 pandemic compared with that previously, although this study did not specifically look at patients' COVID-19 status. Another study by Ishibashi et al 14 found a lower rate of nosocomial infections in patients undergoing gastrointestinal surgery during the COVID-19 pandemic and attributed this decrease to improved infection control practices.…”
Section: Discussionmentioning
confidence: 78%
“…Overall, the impact of the COVID-19 pandemic on SSIs was reported in seven studies [23,25,27,40,43,54,56]. Four of them showed a 14.2% to 60.7% decrease in SSIs during the pandemic [23,43,54,56], and only two studies showed a significant reduction in SSIs [23,56].…”
Section: The Effect Of Covid-19 Pandemic On Surgical Site Infections ...mentioning
confidence: 99%